2007
DOI: 10.1089/aid.2007.0064
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of HIV Type 1 Reverse Transcriptase Mutations in Infants Infected by Mothers Who Received Peripartum Nevirapine Prophylaxis in Jos, Nigeria

Abstract: This study was carried out to characterize HIV-1 reverse transcriptase (RT) mutations in vertically infected infants in Jos, Nigeria. DNA was extracted from peripheral blood mononuclear cells of 102 infants, aged 0 to 6 months, born to HIV-1-infected mothers who had received peripartum single-dose nevirapine prophylaxis. PCR-based diagnosis revealed that 14 infants (13.7%) were infected with HIV-1. Phylogenetic analyses of RT revealed wide viral diversity, with CRF02_AG, subtype G, subsubtype A3, CRF06_cpx, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…CRF02_AG is the fourth most prevalent subtype globally, together with subtype G remain the dominant variants observed in West Africa [6]. In Nigeria, subtypes A, B, C, D, F2, G, J, and group O have been identified along with several CRFs in varying proportions [7][8][9][10]. The distribution of HIV-1 variants in Nigeria seems to differ based on geography, as subtype G is most prevalent in the north and CRF02_AG in the south [8,11].…”
Section: Resultsmentioning
confidence: 99%
“…CRF02_AG is the fourth most prevalent subtype globally, together with subtype G remain the dominant variants observed in West Africa [6]. In Nigeria, subtypes A, B, C, D, F2, G, J, and group O have been identified along with several CRFs in varying proportions [7][8][9][10]. The distribution of HIV-1 variants in Nigeria seems to differ based on geography, as subtype G is most prevalent in the north and CRF02_AG in the south [8,11].…”
Section: Resultsmentioning
confidence: 99%
“…[ 14 15 ] In Nigeria, subtypes A, B, C, D, F2, G, J, and group O have been identified along with several CRFs in varying proportions. [ 16 17 18 19 20 21 22 23 24 25 26 27 ] However, subtypes G and CRF02_AG have been the dominant subtypes in Nigeria and throughout West Africa within the past decade. [ 14 16 19 ] These studies identified HIV-1 subtypes using a variety of laboratory methods such as heteroduplex mobility assays (HMA) and partial genome sequencing of the env , gag , and polymerase ( pol ) genes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 16 19 ] These studies identified HIV-1 subtypes using a variety of laboratory methods such as heteroduplex mobility assays (HMA) and partial genome sequencing of the env , gag , and polymerase ( pol ) genes. [ 16 17 18 19 20 21 22 23 24 25 26 27 ] The distribution of HIV-1 variants in Nigeria seems to differ based on geography, as subtype G is most prevalent in the north and CRF02_AG in the south. [ 20 26 ] Our group has also observed this general subtype distribution and has identified subtypes in complex combinations using MHA and full-length sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…By 1996, a full genome sequence of HIV-1 IbNg had been obtained [10], and analysis proved IbNg to be a complex mosaic genome with segments from subtype A and G, leading to the designation CRF02_AG, of which IbNg is the prototype [11]. Recent studies have shown the predominance of subtypes G and CRF02_AG in Nigeria [12], [13], [14], [15], [16]. In all, HIV-1 subtypes A, B, C, D, F2, G, J and O have been identified in Nigeria, with several recombinant forms, though in varying proportions [15], [17], .…”
Section: Introductionmentioning
confidence: 99%